Exploitation des données de diagnostics en tranchées mécaniques par l’analyse spatiale - Sylvain Badey; Xavier Rodier (Revue Archéologique du Centre de la France)
The archaeological diagnostic consists in assessing the archaeological potential of an area impacted by development. This first phase aims to provide sufficient information -on the nature, extent, chronology and degree of preservation of the sites- to the competent authorities (in France, the Ministry of Culture) in view to prescribe or not an excavation.Beyond the assessment of archaeological potential, they deliver diachronic information on land-use whose exploitation is often restricted. In the case of large areas surveyed, we let’s suppose that the data mining is useful for archaeological interpretation of the site.This paper presents the methods and results of an experiment based on data from a 226 ha archaeological survey performed at Etrechet in Indre (Centre of France). The aim was to evaluate the contribution of spatial analysis, on one hand to read the results of the trial trenching, secondly to understand the land-use in the studied area. The experiment focused on the use of exploratory spatial data analysis. The methods used are both cartographic with the grid analysis and statistic with data clustering. The aim of this methods is to overcome the division imposed by the trial trenches, and consider the whole area.Results show that it is possible to test interpretive hypothesis on the distribution of the remains. Indeed spatial analysis reveals patterns by periods, confronted to the essential archaeological interpretation. The results meet the two objectives of an archaeological assessment. First, they are useful to interpret the remains and to understand the dynamics of land-use. Secondly, as decision-making tool, they provide elements for the authorities to deal with the archaeological sites (excavations or preservation).